Acid Lipase from Candida viswanathii: Production, Biochemical Properties, and Potential Application - Almeida, Alex Fernando de [UNESP]; Tauk-Tornisielo, Samia Maria [UNESP]; Carmona, Eleonora Cano [UNESP] (Hindawi Publishing Corporation, 2013)
Influences of environmental variables and emulsifiers on lipase production of a Candida viswanathii strain were investigated. The highest lipase activity (101.1 U) was observed at 210 rpm, pH 6.0, and 27.5 degrees C. Other fermentation parameters analyzed showed considerable rates of biomass yield (Y-L/S = 1.381 g/g), lipase yield (Y-L/S = 6.892 U/g), and biomass productivity (P-X = 0.282 g/h). Addition of soybean lecithin increased lipase production in 1.45-fold, presenting lipase yield (Y-L/S) of 10.061 U/g. Crude lipase presented optimal activity at acid pH of 3.5, suggesting a new lipolytic enzyme for this genus and yeast in general. In addition, crude lipase presented high stability in acid conditions and temperature between 40 and 45 degrees C, after 24 h of incubation in these temperatures. Lipase remained active in the presence of organic solvents maintaining above 80% activity in DMSO, methanol, acetonitrile, ethanol, acetone, 1-propanol, isopropanol, and 2-propanol. Effectiveness for the hydrolysis of a wide range of natural triglycerides suggests that this new acid lipase has high potential application in the oleochemical and food industries for hydrolysis and/or modification of triacylglycerols to improve the nutritional properties.